Orthodontics in public health policies: literature review (Research, Society and Development, 2022)
Introduction: With the objective of modifying the previously used health care model, the Unified Health System (SUS) was created. The National Health Policy, known as “Smiling Brazil” was developed to ensure prevention, promotion and recovery of the oral health of the Brazilian population. Dentistry, for a long time, was judged as an area of ​​no importance by public health policies, being offered most of the time only extraction treatments. With the implementation of the Dental Specialty Centers, other specialties started to be offered by the SUS, including orthodontic treatment. Objective: To develop a narrative review of the literature on the inclusion of orthodontic treatment in public health policies, demonstrating the importance of the presence of orthodontics in the SUS and its effectiveness. Methodology: The articles used were through PubMed, Scielo, Web of Science and Google Scholar databases between the years 2000 to 2022. Results: Contribution, through a literature review, so that there is optimization of orthodontic care in the Unified Health System and greater investment in this area. Final considerations: It is concluded that preventive and interceptive orthodontic treatment should be an accessible practice in public health, as malocclusions can cause consequences in the life of the individual that go beyond aesthetics, such as the difficulty of social insertion.